The development of a behavior checklist for mentally tough behaviors in volleyball - Madrigal, L. (The Sport Psychologist, 2020)
Mental toughness is a factor related to performance, better coping, and increased confidence. There has been a growing trend toward assessing mental toughness behaviorally. The purpose of this paper was to develop a behavioral assessment of mental toughness in volleyball. Following a five-stage process to develop a systematic observation instrument, the current study identified 10 mental toughness behaviors in volleyball, specifically, six behaviors occurring during a play and four behaviors after a play (i.e., when a point is scored from the opposing team). Furthermore, eight behaviors represent mentally tough actions, while two behaviors represent mentally weak actions. The results indicate that the behavioral checklist is a reliable systematic observation instrument. Coaches and certified mental performance consultants can benefit from using this checklist by discussing mental toughness and behaviors corresponding to mental toughness during game play, and then have a quantifiable way to track behaviors with individuals and volleyball teams.